2017
DOI: 10.1001/jama.2017.1371
|View full text |Cite
|
Sign up to set email alerts
|

Association of Preceding Antithrombotic Treatment With Acute Ischemic Stroke Severity and In-Hospital Outcomes Among Patients With Atrial Fibrillation

Abstract: Among patients with atrial fibrillation who had experienced an acute ischemic stroke, inadequate therapeutic anticoagulation preceding the stroke was prevalent. Therapeutic anticoagulation was associated with lower odds of moderate or severe stroke and lower odds of in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 193 publications
(153 citation statements)
references
References 36 publications
10
136
0
7
Order By: Relevance
“…The underutilisation of OAC is a substantial public health issue . While it is difficult to assess the extent of adverse events accurately due to this issue, the number of patients presenting to hospital with a stroke and AF while not anticoagulated is well described . It is, therefore, of paramount importance to identify why OAC is underutilised, including whether availability of specialised clinics is a factor.…”
Section: Discussionmentioning
confidence: 99%
“…The underutilisation of OAC is a substantial public health issue . While it is difficult to assess the extent of adverse events accurately due to this issue, the number of patients presenting to hospital with a stroke and AF while not anticoagulated is well described . It is, therefore, of paramount importance to identify why OAC is underutilised, including whether availability of specialised clinics is a factor.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of more than 90,000 patients with acute ischemic stroke and prior atrial fibrillation determined that 30% were not on antithrombotic therapy, and ~40% received an anti-platelet agent only [189]. Two-thirds had no documented reason as to why anticoagulation was withheld, but for those with a documented reason, bleeding (16%) and falls (10%) were cited most often.…”
Section: Future Directionsmentioning
confidence: 99%
“…However, oral anticoagulants are especially underused in patients with known nonvalvular AF in China (Wang et al, ). Several studies have demonstrated that preceding oral anticoagulants are associated with reduced initial stroke severity on admission and reduced disability or death at discharge in IS patients with AF (O'Donnell et al, ; Xian et al, ). These results were consistent with our study.…”
Section: Discussionmentioning
confidence: 99%